Detection of naegleria species in environmental samples from peninsular Malaysia - Ithoi, I.; Ahmad, A.F.; Nissapatorn, V.; Lau, Y.L.; Mahmud, R.; Mak, J.W. (Public Library of Science, 2011)
BACKGROUND: In Malaysia, researchers and medical practitioners are unfamiliar with Naegleria infections. Thus little is known about the existence of pathogenic Naegleria fowleri, and the resultant primary amoebic meningoencephalitis (PAM) is seldom included in the differential diagnosis of central nervous system infections. This study was conducted to detect the presence of Naegleria species in various environmental samples.